Development of a mango rum coulis for a Puerto Rican-style mango rum cake - Johnson, Kyle; Phalen, Kyle; Weber, Austin; Manville, Erin; Getty, Kelly J.K. (My University, 2017)
People desire convenience foods such as desserts that can be easily microwaved and consumed. A microwavable Puerto Rican-style mango rum cake was developed and it was determined that a tropical fruit sauce (coulis) would improve the flavor, appearance, and texture of the cake. The objective of this research was to develop a mango rum coulis that could be drizzled over the mango rum cake. To begin the development process, research trends determined mango as a popular tropical fruit along with spiced rum being used in Puerto Rican cuisine. Initially, a mango puree and pineapple juice was reduced and then spice rum was added at the end of the process. The reduction process resulted in an unacceptable acidity level and the alcohol was cooked off while maintaining the rum flavor. The next step was to mask the acidity by testing varying amounts of cane sugar, coconut sugar, or powdered sugar. The initial formulation prior to reduction consisted of 49.1% canned mango puree, 29% pineapple juice, 11.2% sugar variant, and 10.8% spice rum. The addition of sugar resulted in a gritty texture, a caramel flavor profile, and a sweeter overall flavor profile. Due to inconsistent results, a mango rum coulis (thin fruit puree used as a sauce) was developed that could be easily frozen and then thawed to drizzle on top of the mango rum cake. Ingredients of the mango rum coulis were canned mango 60.7%, orange juice 36.4%, rum extract 5.0%, lemon juice 4.6%, xanthan gum 0.31%, cinnamon 0.30%, and clove 0.30%. The canned mango was strained twice to reduce moisture content. The functional ingredient xanthan gum stabilized the structure of the coulis through freezing and reheat and thickened the coulis. Rum extract eliminated the alcohol content, intensified the rum flavor, and widened the market to all ages. The final mango rum coulis formation had a pH of 4.6. It was determined that 30 g of coulis on one serving of cake (193 g) provided an ample coulis to cake ratio. The final mango rum coulis formulation paired well to the mango rum cake that added freshness, an all-natural sweetener, and spiced rum flavor without the alcohol. This product will appeal to the health conscious and on-the-go consumer.
Keywords: Spring 2017